2020
DOI: 10.1111/liv.14725
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps enhance procoagulant activity and thrombotic tendency in patients with obstructive jaundice

Abstract: Background & Aims Patients with obstructive jaundice (OJ) are considered to be prothrombotic with increased risk of thromboembolism complications. The role of neutrophil extracellular traps (NETs) in procoagulant activity (PCA) and thrombosis risk in patients with OJ is unclear. In this study, we investigated NETs formation in OJ patients and the role of elevated unconjugated bilirubin (UCB) in inducing NETs, resulting in enhanced PCA and endothelial injury. Methods NETs of OJ patients and healthy controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Based on accumulating evidence, neutrophils play a key role in the process of thrombosis (5)(6)(7)(8). The depletion of neutrophils has been shown to reverse experimental thrombosis (9,10). Another study reported that neutrophils produce tissue factor (TF) and contribute to the formation of thrombosis in vivo and in vitro (11).…”
Section: Introductionmentioning
confidence: 99%
“…Based on accumulating evidence, neutrophils play a key role in the process of thrombosis (5)(6)(7)(8). The depletion of neutrophils has been shown to reverse experimental thrombosis (9,10). Another study reported that neutrophils produce tissue factor (TF) and contribute to the formation of thrombosis in vivo and in vitro (11).…”
Section: Introductionmentioning
confidence: 99%
“…Research into procoagulant activity, specifically by measuring coagulation time, fibrin formation, and purified coagulation complexes, has revealed that the presence of neutrophil extracellular traps (NETs) in patients with OJ is significantly higher than in healthy individuals. This suggests that targeting NET values could be a promising approach to improving coagulation disorders in OJ patients[ 50 ]. Cakir et al [ 51 ] conducted a study that observed hypercoagulability in more than half of patients with OJ.…”
Section: Pathophysiological Consequencesmentioning
confidence: 99%
“…Elevated levels of NETs have been correlated with poor prognosis in liver diseases, such as NASH 19 and HCC 20 . Our previous study indicated increased NET levels in the circulation of patients with CLD due to heightened bilirubin, with these NETs amplifying circulation coagulation activity in patients with CLD 21 . In CLD, accumulating large bilirubin in the liver prompts activated KCs to release chemotactic factors, recruiting neutrophils.…”
Section: Introductionmentioning
confidence: 97%
“…[20] Our previous study indicated increased NET levels in the circulation of patients with CLD due to heightened bilirubin, with these NETs amplifying circulation coagulation activity in patients with CLD. [21] In CLD, accumulating large bilirubin in the liver prompts activated KCs to release chemotactic factors, recruiting neutrophils. However, the presence of NETs in the liver in CLD and their role in promoting liver coagulation activity remain undetermined.…”
Section: Introductionmentioning
confidence: 99%